ENVIRONMENTAL SUITABILITY, PLANTING DENSITY AND INDUSTRIAL PERFORMANCE OF INTENSIVE VANAME (Penaeus vaname ) FISHING IN PONDS - Farkan, Mochammad; Sektiana, Sinar Pagi; Nurraditya, Lakonardi; Pamaharyani, Luchiandini Ika; Lathifah, Firyal (Politeknik Kelautan dan Perikanan Dumai, 2024)
Shrimp is one of the leading commodities with high economic value and generates foreign exchange in local and international markets. The production of shrimp farming industry in ponds fluctuates, causing doubts for investors and practitioners to develop shrimp farming in ponds. The weakness is that there is no available data on the evaluation of aquaculture performance as a good shrimp farming planning material. The purpose of this study was to assess the performance of shrimp farming industry in intensive pond system. The research was conducted from September 2023 to February 2024. The research location was Rhee Royal Vannamei Sumbawa West Nusa Tenggara, Indonesia. This research is applied research with data collection methods are observation and quantitative. Data processing using Microsoft excel and SPSS (Statistical Program for Social Science). The results showed that the land is suitable for vaname shrimp farming, performance analysis showed Average daily growth (ADG) 0.4 gr/day, Average body weight (ABW) 13.86+5.59 g/head, Survival Rate (SR) 55+25%, Food Conversation Ratio (FCR) 1-1.5, and Productivity 11+5 tonnes/ha. The relationship between stocking density and shrimp productivity was not significant. Five cycles of production fluctuate, so it is not possible to determine predictions for the coming year. The prospect of shrimp farming industry in ponds is good enough to improve the economy.